Competitive Personalized Pricing - Chen, Zhijun; Choe, Chongwoo; Matsushima, Noriaki (Management Science, 2020)
We study a model where each competing firm has a target segment where it has full consumer information and can exercise personalized pricing, and consumers may engage in identity management to bypass the firm’s attempt to price discriminate. In the absence of identity management, more consumer information intensifies competition because firms can effectively defend their turf through targeted personalized offers, thereby setting low public prices offered to nontargeted consumers. But the effect is mitigated when consumers are active in identity management because it raises the firm’s cost of serving nontargeted consumers. When firms have sufficiently large and nonoverlapping target segments, identity management can enable firms to extract full surplus from their targeted consumers through perfect price discrimination. Identity management can also induce firms not to serve consumers who are not targeted by either firm when the commonly nontargeted market segment is small. This results in a deadweight loss. Thus, identity management by consumers can benefit firms and lead to lower consumer surplus and lower social welfare. Our main insight continues to be valid when a fraction of consumers are active in identity management or when there is a cost of identity management. We also discuss the regulatory implications for the use of consumer information by firms as well as the implications for management. This paper was accepted by Juanjuan Zhang, marketing.